A wearable system assessing relevant characteristics of the whole ski jumping sequence - Chardonnens, J.; Favre, J.; Cuendet, F.; Gremion, G.; Aminian, K. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Some descriptive biomechanical parameters have been identified to be related to ski jumping performance (e.g. lift force). However, measuring these parameters is a non trivial task which requires complex devices, well trained staff and time consuming post-processing. Therefore, these parameters are almost never considered in daily training, but rather limited to research projects. The first aim of this study was to propose a system to capture the athlete movement during the entire jump that is compatible with daily training requirements. The second aim was to assess the relevance of angular, coordination and dynamic parameters automatically calculated by the proposed system.